Evaluation of Factors Related to Postoperative Complications in Patients Who Underwent Reduction Mammoplasty - Gaye Toplu; Dinçer Altınel; Merdan Serin (European Journal of Breast Health, 2021)

(untitled)
Objective:This study aimed to investigate whether there was an increase in the number of postoperative complications in patients undergoing reduction mammoplasty depending on the technique used (i.e., pedicle type, skin incision pattern), existence of concomitant diseases, and presence of other risk factors.Materials and Methods:A total of 186 patients who underwent breast reduction between 2013 and 2018 (bilateral, n = 170; unilateral, n = 16) were included in the study. A retrospective review of the data of patients who underwent reduction mammoplasty, which was performed by the same surgical team in a single institution over a 6-year period, was carried out. Superomedial, superior, and inferior pedicles were used in 99, 55, and 32 patients, respectively. The median follow-up period was 4 years.Results:The median patient age was 45 (range: 16–75) years. The median total reduction weight was 2,194 (range: 80–4,800) grams. The median distance between the sternal notch and nipple was 31 cm (range: 24–45 cm) for the right breast and 30 cm (range: 22–45 cm) for the left breast. The overall complication rate was 6.9%. The complication rates in patients with and without any concomitant diseases were 10.2% and 4.6%, respectively. The overall complication rate was significantly higher in patients with smoking habit, accessory breasts, progesterone use, cerebrovascular disease, morbid obesity (Body Mass Index ≥40 kg/m2), and thalassemia.Conclusion:Our analysis shows that the presence of concomitant diseases increases the risk for postoperative complications in patients who underwent reduction mammoplasty. Our findings do not suggest that any of the techniques have significant superiority to each other in terms of pedicle safety and overall complication rate.